Phytochemical composition and 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity of Anthocleista vogelii (Gentianaceae) root extract - Aiwonegbe, Anthony; Ojeniyi, Olarotimi; Akhidenor, Faith I.; odion, Emmanuel (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: Anthocleista vogelii Planch (Gentianaceae) is an evergreen tree with support root system, native to West Africa with rich sources of polyphenols and used as medicine traditionally for treating ailments related to oxidative stress caused by free-radicals produced from metabolic process. Aims: Thus this study aims to screen for phytochemicals in the crude extract of A. vogelii root, quantify the polyphenolic contents and evaluate it radical scavenging potential. Methods: Established standard protocol of color and precipitation formation was used to screen for the phytochemicals in the crude extract of A. vogelii root. Folic-Ciocalteu reagent was used to quantify the phenolic compound, while aluminum chloride was utilized in determining the flavonoids content. The antioxidant potential was evaluated using 2,2-diphenyl-1-picrylhydrazyl radical scavenger (DPPH). Results: Preliminary screening reveals alkaloids, tannins, phenolics, flavonoids, glycosides, terpenoids and saponins. The crude extract of A. vogelii gave total phenolic content and total flavonoid content of 24.87±2.12 mgGAE/g and 16.18±0.54 mgQE/g respectively. The radical scavenging potential of the extract compared well with ascorbic acid standard with IC50 of 14.08 µg/mL. Conclusion: The methanol root extract of A. vogelii contain phytochemicals, especially flavonoids and phenolics responsible for it radical scavenging activity.